Current progress in human genetics - Williams, Mark (United States : c, 2021)
The study of inheritance in human beings is referred to as human genetics. It is a multidisciplinary field that encompasses various fields such as molecular genetics, classical genetics, genomics, cytogenetics, biochemical genetics, population genetics, developmental genetics and clinical genetics. Genes are the common factors of the qualities of most human-inherited characteristics. A few major inheritance patterns are autosomal dominant inheritance, X-linked and Y-linked inheritance and autosomal recessive inheritance. Human genetics is an important field that helps to find the answers regarding human nature. It can also help in understanding various diseases and their effective treatment. This book outlines the processes and applications of human genetics in detail. From theories to research to practical applications, case studies related to all contemporary topics of relevance to this field have been included herein. Those in search of information to further their knowledge will be greatly assisted by this book.
Keywords: Bioinformatics; Human genetics